Pencegahan Fraud Dalam Memediasi Pengendalian Internal Dan Kompetensi Dalam Rangka Good Governance - Cahyanto, Agus Budi; Askafi, Eka; Mulyaningtyas, Ratna Dewi; Mutiara, Nisa (Universitas Islam Kadiri, 2025)
The government is currently facing many demands on its performance. The Indonesian people expect a better governance system and eliminate the practice of KKN (Corruption, Collusion and Nepotism). In addition to these expectations, the government is required to always provide better, faster and more effective services to all levels of society. These demands also include the fiscal sector, namely the Customs institution. Customs is also required to improve itself to create better governance in order to create effective and efficient services. To create this, Internal Control, increased competence and efforts to prevent Fraud are needed to achieve Good Governance. The study aims to determine the relationship between internal control, competence, Fraud prevention and implementation of Good Governance using a quantitative approach carried out at Kediri Customs through the distribution of questionnaires with SEM PLS data analysis tools. The results of data processing show that all variable indicators meet validity and reliability, and meet the goodness of fit model. Of the seven hypotheses, three cannot be accepted, especially in the relationship between Fraud prevention and the implementation of Good Governance.